LEGAL ANALYSIS REGARDING LEGAL ARRANGEMENTS FOR HANDLING THE CRIME OF DEFAMATION THROUGH ELECTRONIC MEDIA BASED ON RESTORATIVE JUSTICE - Andry Syafrizal Tanjung (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
The restorative justice approach is an alternative resolution action outside of court that prioritizes peace and restitution of losses and aims to empower victims, perpetrators, families and the community to repair an unlawful act by using awareness and conscience as a basis for improving social life. This research was conducted using normative legal research. After carrying out a legal analysis of the Circular Letter of the Chief of Police of the Republic of Indonesia Number SE/2/11/2021 concerning Awareness of Ethical Culture to Create a Clean, Healthy and Productive Indonesian Digital Space and the Republic of Indonesia State Police Regulation Number 8 of 2021 concerning Handling Criminal Acts Based on Restorative Justice, peace can be made for criminal acts of defamation through electronic media with a restorative justice approach, but it must comply with applicable requirements and procedures.